2020
DOI: 10.3390/nu12041143
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ganoderma lucidum (Ganodermataceae, Basidiomycota) as Radioprotector

Abstract: For millennia, naturopaths and physicians have used Ganoderma lucidum (reishi mushroom) for its diverse therapeutic properties, as recorded in the oldest Chinese herbal encyclopedia. Indeed, a radioprotective effect has been reported in the isolated components of its extracts. A systematic review and meta-analyses (PRISMA) was conducted in March 2020, searching databases including PubMed, Scopus, Embase, and Google Scholar, along with Clinical Trials. The inclusion criteria were ex vivo, in vitro, and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Besides, Reishi found numerous applications in treating hepatitis, arthritis, asthma, insomnia, gastric ulcers, and neurasthenia (González et al, 2020;McKenna, 2002;Zahid, Barua, & Huq, 2010;. Traditionally, Reishi has been used after boiling and drying for the treatment of various ailments (Cho et al, 2012).…”
Section: Traditional or Folk Lore Uses Of Reishimentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Reishi found numerous applications in treating hepatitis, arthritis, asthma, insomnia, gastric ulcers, and neurasthenia (González et al, 2020;McKenna, 2002;Zahid, Barua, & Huq, 2010;. Traditionally, Reishi has been used after boiling and drying for the treatment of various ailments (Cho et al, 2012).…”
Section: Traditional or Folk Lore Uses Of Reishimentioning
confidence: 99%
“…Reishi remained a traditional therapy for shortness of breath, palpitation, dizziness, and insomnia (Wachtel‐Galor et al, 2011). Besides, Reishi found numerous applications in treating hepatitis, arthritis, asthma, insomnia, gastric ulcers, and neurasthenia (González et al, 2020; McKenna, 2002; Zahid, Barua, & Huq, 2010; S. Zhou & Gao, 2002). Traditionally, Reishi has been used after boiling and drying for the treatment of various ailments (Cho et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ganoderma lucidum (G. lucidum) belongs to basidiomycete, with a woody texture, widely distributed in tropical and temperate regions in Europe, North America, and Asia [1]. It is a kind of mushroom for both medicine and food, which has a long history in China, Japan, Korea, and other Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…As a functional medicine and food for the amelioration of health and longevity, Ganoderma species have been used in Traditional Chinese Medicine (TCM) for more than two millennia ( Fu et al, 2019 ; Leskosek-Cukalovic et al, 2010 ). Ganoderma species are considered legal crude drug medicines in the Chinese Pharmacopoeia (2015 edition) for preventing cancer, neurodegeneration, and cardiovascular diseases in the clinic stage ( Chung et al, 2017 ; González et al, 2020 ). In addition, modern pharmacological and clinical investigations have also demonstrated that Ganoderma species have various pharmacological effects and biological activities such as antioxidant, anti-inflammatory, antiaging, antitumor, and hepatoprotective, and other medicinal activities.…”
Section: Introductionmentioning
confidence: 99%
“…( Fujita et al, 2005 ; Martínez-Montemayor et al, 2019 ). The main bioactive compounds include triterpenoids, polysaccharides, sterols, and proteins extracted from its fruiting bodies (basidiocarps), which are responsible for these biological activities of Ganoderma species ( Chung et al, 2017 ; González et al, 2020 ). Among them, triterpenes are one of the main active components of Ganoderma lucidum , which inhibit various inflammatory reactions in vivo ( Feng and Wang, 2019 ; C. Liu et al, 2015 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%